Fiber-optic intelligence systems for diagnostics contraction integrity of aircrafts - Shevchuk, Dmytro O. (Proceedings of National Aviation University, 2010)
Article is devoted to the possibilities to use the fiber-optical intelligence structure for the diagnostics contraction integrity of aircrafts